Assessment of knowledge regarding menstruation and practices related to maintenance of menstrual hygiene among the women of reproductive age group in a slum of Kolkata, West Bengal, India - Santra, Sutanuka (International Journal Of Community Medicine And Public Health, 2017)
Background: Menstruation is a normal biological process and a key sign of reproductive health. Unfortunately, the taboo surrounding menstruation prevents women from articulating their needs. There is lack of awareness on the process of menstruation and hygienic management of the same. So, the problem of poor menstrual hygiene still persists in society. Objectives: 1) To elicit the knowledge regarding menstruation among the women of reproductive age group 2) To find out the practice of menstrual hygiene among them. Methods: A community based, observational, cross-sectional study was conducted at Baghbazar slum, Kolkata. A total of 160 menstruating women of the age group between 15-45 years were included. The data were analysed using IBM SPSS version 20. Results: Only 32 women (20%) had idea before menarche regarding menstruation. 65% women used only sanitary pad and 30% used only cloth pieces where as 5% used both pad and cloth piece. Prevalence of sanitary pad use was significantly higher among those aged <25 years (p<0.05). With increasing literacy status as well as socio economic status, use of sanitary pad was also found to be increased and this difference was statistically significant (p<0.05). About 42% of the cloth piece users reused cloth piece. All those, who reused cloth pieces, washed the used cloth pieces with soap and water and 50% of them dried those under sunlight. All the women practised some kind of restriction during menstruation. About 4% individuals did not take regular bath during their bleeding period. Some women (37.5%) suffered from reproductive tract infection during or just after menstruation. Most of the study subjects (95.6%) disposed used napkins in municipal vat. Conclusions: Awareness should be increased regarding maintenance of good menstrual hygiene through health education programme.